Les mots étrangers dans Dream of Fair to Middling Women (1932) de Samuel Beckett - Pascale Sardin (Revue LISA)
This article focuses on the place of foreign words and citations in Samuel Beckett’s first novel written in the years 1931-1932. Greatly influenced by James Joyce and by the avant-garde of the times, the young Irish poet scattered his text with opaque terms, various intertexts and multilingual puns. Contrary to Joyce though, he did not intend to reach an apotheosis of the word. Rather, he wished to form a disjointed aesthetic and pave the way for the literature of the “unword” he would soon strive to create. This strategy is discussed in the context of the author’s life and of his adoption of a bilingual mode of writing that took place a few decades later.